PEMIMPIN YANG MENGHAMBA, BUKAN DIPERHAMBA - Dr. Harun Y. Natonis, S.Pd, M.Si (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2019)
The church and politics in Indonesia are two opposing institutions, but live side by side. On the one hand, the church is prohibited from engaging in various political contexts. But on the other hand, the church also has an obligation to voice the truth in a political context. The church is not involved in the political world, it does not mean that the church turns a blind eye to the political conditions that occur in Indonesia. The church have to give voice its prophethood, so that the political conditions in Indonesia continue to provide a temperature of comfort and justice for all the interests of society.The church is like a small candle which despite its small flame, gives enough light in dark conditions. The Church through its leaders can provide encouragement in actualizing services that are more real amid the development of the nation in competition in the global world.What kind of leader does the church need to survive amid the current political turmoil in Indonesia? This question is the core goal of writing this article in order to address the extent of the role of the church in the midst of a political vortex.The church needs servant leaders, not leaders who are enslaved. Church leaders who are servants are church leaders who want to serve with love, humility and sincere sacrifice. While church leaders who are worshiped are church leaders who are only concerned with personal interests and self-comfort. Church leaders who are able to survive in the midst of political turmoil are church leaders who are servants, not non-worshiped church leaders.Keywords: Church leader who slaves, Jesus Prototype Leader who slaves